Epigenetic regulation of microRNA expression in Hodgkin lymphoma. Issue 9 (2nd September 2015) - Navarro, Alfons; Díaz, Tania; Cordeiro, Anna; Beyá, Marina Díaz; Ferrer, Gerardo; Fuster, Dolors; Martinez, Antonio; Monzó, Mariano
Abstract : Epigenetic mechanisms are crucial for the inactivation of key genes related to the survival of Hodgkin lymphoma (HL) cells, and methylation is a frequent epigenetic mechanism of microRNA silencing. We have examined the methylation-induced silencing of tumor suppressor microRNAs in HL cell lines and confirmed our results in patient lymph nodes. In addition, we evaluated the in vitro effectiveness of 5-aza-2-deoxycytidine (5-Aza-dC) in HL cell lines. Ten microRNAs containing CpG islands in their promoter region were re-expressed in both the L-428 and L-1236 cell lines. Interestingly, miR-34a and miR-203, both known tumor suppressor microRNAs, were found to be methylated in cell lines and in patient samples. 5-Aza-dC treatment resulted in a dose-dependent antiproliferative effect at 72 h in all the HL cell lines. In summary, 5-Aza-dC treatment of HL cell lines inhibits proliferation at high doses and produces re-expression of the tumor suppressor microRNAs at low-intermediate doses.